Multiscale water diffusivity prediction of plain woven composites considering void defects - Wang Meng (Science and Engineering of Composite Materials, 2024)
To reveal the effects of void defects on the diffusivities of plain woven composites, a multiscale analysis framework considering the microscale and mesoscale voids is developed in this study. Different void modeling methods and analysis strategies are used to reveal the effects of void size, void shape, and void modeling assumptions on the equivalent diffusivities of the tows and plain woven composites. The analysis results show that the transverse or longitudinal diffusivities of tows predicted with an element-based modeling method are larger than those with void shapes considered. Considering void shape results in the variation of the predicted diffusivities. Based on the uniform assumption used for modeling the voids in the tows, the through-thickness and in-plane diffusivities are found to be dependent on the transverse and longitudinal diffusivities, respectively. Based on the element-based void modeling method for the tows, the predicted values are larger than those based on the uniform assumption. These tow void modeling methods cannot result in variation within predicted values. The effects of void shapes in the pure matrix on the diffusivities are also revealed, and the variation is observed.